High-stability colored high-temperature nylon material and preparation method thereof
By introducing specific structural masterbatches into high-temperature nylon materials, the problems of color change and weather resistance of high-temperature processing are solved, and the preparation of high-stability color high-temperature nylon materials is achieved, which significantly improves the material's resistance to boiling and discoloration and weather resistance.
Patent Information
- Application Number
- CN202411909043.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
AI Technical Summary
High-temperature nylon materials are prone to oxidation and yellowing during processing and use, especially colored products are prone to color change in high temperature environments, and the existing technology is difficult to effectively solve this problem.
Using specific structural masterbatches, including carrier resin, structural toner and dispersant, melt extrusion, granulation and drying are carried out through a twin-screw extruder to prepare high-stability colored high-temperature nylon materials.
The color change effect of high-temperature processing is significantly improved, the material's resistance to boiling and weathering resistance is improved, and the dispersion problem of structural toner is solved, expanding its application in the field of thermoplastic materials.
Smart Images

Figure BDA0005205152980000051 
Figure BDA0005205152980000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high-stability colored high-temperature nylon material and a preparation method thereof. Background Art
[0002] Nylon has received more and more attention since its advent. However, due to the high processing temperature and its own group characteristics, nylon is easily oxidized and yellowed during processing and use, especially indigo, red, orange and other colored products, which are easily affected by processing windows, part structure, machine size, production rhythm, etc. to produce color changes. How to reduce the color change of such materials under high-temperature processing, water absorption and humidity, outdoor weather resistance and other environments has become a major problem in the prior art. Patent CN113201216B modifies the product by using a specific content of cerium sulfide as a colorant, and the resulting nylon is firmly colored, significantly improving its 280°C heat-resistant retention color change and moisture absorption color change. Patent CN112358722B uses a suitable proportion of solvent red 179, pigment red 178 and pigment red 265 for compounding, and the addition of a dispersion stabilizer, synergistic effect, can significantly reduce the color difference of polyamide composite materials after water absorption. High-temperature nylon refers to a special nylon material with a melting point generally higher than 290°C, which can be used for a long time in an environment above 150°C. Due to the higher melting point of high-temperature nylon, it is more likely to change color during extrusion granulation, injection molding processing and other links, and related improvement plans are rarely reported.
[0003] Structural color is a phenomenon in which visible light produces special optical reflection, refraction, diffraction, interference and other phenomena with certain structural features at the micrometer or nanometer scale, so that the human eye can receive high-purity, high-brightness, and changing colors. Common examples in life include: CDs, soap bubbles, shells, rainbows, and butterfly wings. In recent years, many literatures have reported the application of structural colors in the fields of coatings, textile dyeing and finishing, glass, cement, etc. For example, patent CN115160872A discloses the application of nanostructured color powder in automobile paint coatings, which can achieve brighter, purer, and higher gloss colors with colored primer layers and varnish layers. Patent CN113897789B immerses the yarn body with an adhesive layer in a color paste, and solidifies the color paste to form a photonic crystal layer, which can easily achieve the intersection of multiple hues on the same fabric or textile. Patent CN114524613B adds nanostructured color powder to high-temperature molten glass liquids such as silicon dioxide, aluminum oxide, and sodium oxide to obtain heterochromatic glass, which increases the diversity of color types. Patent CN104556899B utilizes hollow structure color powder as slow-release color powder, and combines it with polymer latex, cement, quartz powder, redispersible rubber powder, and functional additives to obtain a post-colored polymer cement waterproof coating, providing a product with personalized color characteristics.
[0004] However, due to problems such as the dispersion of structural color powder, its application is limited to dyeing, finishing, painting and other fields, and its application in thermoplastic materials has rarely been reported. Summary of the invention
[0005] Based on the defects of the prior art, the purpose of the present invention is to provide a high-stability colored high-temperature nylon material, which effectively solves the processing color change defect of colored high-temperature nylon by introducing a specific structure masterbatch. At the same time, the obtained product's resistance to water boiling and discoloration and weather resistance are also significantly improved.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A high-stability colored high-temperature nylon material comprises the following raw materials in parts by weight:
[0008] High temperature nylon 40-98 parts;
[0009] 1-5 parts of structural masterbatch;
[0010] 1-3 parts of color powder;
[0011] Filler 0-60 parts;
[0012] Conventional additives 0.5-5 parts.
[0013] In colored high temperature nylon material,
[0014] The high temperature nylon is selected from homopolymers or copolymers such as PA6T / 66, PA6T / DT, PA6T / 6I, PA10T, PA9T, PA10T / 66, and PA11T; the melting temperature of the high temperature nylon is 290-340°C.
[0015] The structural color masterbatch comprises the following components in parts by weight: 70-90 parts of carrier resin; 10-30 parts of structural color powder; and 0.5-5 parts of dispersant.
[0016] In structural masterbatch,
[0017] The carrier resin is a liquid crystal polymer (LCP), preferably with a melting temperature of 270 to 330°C. The melting point of the structural masterbatch is ≤ the melting point of high-temperature nylon. The structural color powder is a powdered optical crystal with a periodic micro-nano structure of the size of the wavelength of light; specifically, the metal or its oxide is vacuum-plated to obtain a nano-structured film layer, and then prepared by distilled water stripping, ultrasonic crushing, drying, particle size screening and other processes; more specifically, the metal or its oxide includes one or more of aluminum, copper, aluminum oxide, titanium oxide, and iron oxide, and the vacuum plating process includes one or more of vacuum evaporation, sputtering, and magnetron sputtering. The dispersant is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide.
[0018] In colored high temperature nylon material,
[0019] The color powder is selected from inorganic pigments, organic pigments, dyes, etc. From the perspective of high-temperature nylon applications, it is preferably heat-resistant above 300°C.
[0020] The filler includes reinforcing fiber, powder, flame retardant, etc. The reinforcing fiber includes one or more of glass fiber (GF), aramid fiber (AF), carbon fiber (CF), basalt fiber (BF); the powder includes one or more of wollastonite, glass microspheres, magnesium sulfate whisker, talcum powder, calcium carbonate, wood powder; the flame retardant includes one or more of halogen flame retardant, nitrogen flame retardant, phosphate flame retardant.
[0021] The conventional auxiliary agent includes one or a mixture of lubricants, mold release agents, nucleating agents, antioxidants, light stabilizers, fluorescent brighteners, and toughening agents.
[0022] The method for preparing the above-mentioned high-stability colored high-temperature nylon material comprises the following steps:
[0023] (1) Preparation of structural color masterbatch: weigh the raw materials according to the formula ratio; add the liquid crystal polymer, structural color powder and dispersant through the main feeding port of the twin-screw extruder after mixing, and obtain the structural color masterbatch after melt extrusion, granulation and drying at a temperature of 300-330° C. for standby use;
[0024] (2) Preparation of modified materials: After the above-mentioned high-temperature nylon, structural masterbatch, color powder, filler and conventional additives are mixed, except for the reinforcing fiber added from the side feed, the other mixed components are added through the main feed port of the twin-screw extruder, and the composite material is obtained after melt extrusion, granulation, drying and other processes at a temperature of 300-330°C.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention achieves a significant improvement in the discoloration during high-temperature processing by combining specific types of color powder and additives, and at the same time, the resulting product also has significantly improved resistance to discoloration during boiling water and weathering.
[0027] (2) The structural color masterbatch used in the present invention solves the problem of the dispersibility of the structural color powder on thermoplastic materials, significantly reduces the amount of structural color powder used, and only a small amount is needed to obtain a good coloring effect without adding additional formula costs, thereby expanding the application of structural color powder in the field of thermoplastic materials.
[0028] On the one hand, the present invention utilizes the characteristics that the carrier resin liquid crystal polymer becomes a high-fluidity liquid crystal at a specific temperature and is highly oriented and ordered, so as to achieve structural color powder enrichment on the surface and present a very good planar arrangement orientation; on the other hand, the dispersant N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide will transform from a powder form to a three-dimensional needle structure under high temperature conditions, and due to its unique multi-dimensional structure, the dispersion and distribution of the color powder are further optimized. DETAILED DESCRIPTION
[0029] In order to make the technical solution of the present invention clearer and more specific, the present invention is further described below. Any equivalent replacement of the technical features of the technical solution of the present invention and any solution derived by conventional reasoning shall fall within the protection scope of the present invention.
[0030] The materials used in the present invention are as follows:
[0031] High temperature nylon 1: PA6T / 66, melting point 300°C, commercially available
[0032] High temperature nylon 2: PA10T, melting point 320°C, commercially available
[0033] High temperature nylon 3: PA4T, melting point 340°C, commercially available
[0034] Liquid crystal polymer 1: LCP K280, melting point 280°C, Shanghai Pulit Chemical New Materials Co., Ltd.;
[0035] Liquid crystal polymer 2: LCP Z330, melting point 330°C, Shanghai Pulit Chemical New Materials Co., Ltd.;
[0036] Liquid crystal polymer 3: LCP S360, melting point 360°C, Shanghai Pulit Chemical New Materials Co., Ltd.;
[0037] Structural color powder 1: red, commercially available
[0038] Structural color powder 2: yellow, commercially available
[0039] Structural color powder 3: blue, commercially available
[0040] Red powder: Homemade color powder pack
[0041] Yellow powder: Homemade color powder pack
[0042] Blue powder: Homemade color powder bag
[0043] Dispersant: N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxylate, commercially available Processing stabilizer: commercially available
[0044] Glass fiber: 568H, commercially available
[0045] Lubricant: A-C540A, commercially available
[0046] Antioxidant: GA-80, commercially available
[0047] Antioxidant: S9228, commercially available
[0048] The structural color masterbatch was prepared according to the formula described in Table 1. The composite material was prepared according to the formula and dosage described in Table 2. The initial color was based on the color matching to red (L=45±0.5, a=45±0.3, b=15±0.3), yellow (L=75±0.5, a=0±0.3, b=50±0.3), and blue (L=50±0.5, a=-15±0.3, b=-30±0.3).
[0049] Product performance test method:
[0050] (1) Sample size: 70*50*3mm, L, a, b values were tested by Minolta CM-2500C colorimeter. The sample was injected at 320℃ on an injection molding machine as a color plate for conventional molding.
[0051] (2) Discoloration during processing: The injection molding machine is used to hold the injection at 330°C for 5 minutes, and the color difference is compared with the color plate of conventional molding to obtain △E.
[0052] (3) Extreme high temperature processing discoloration: The color difference is obtained by comparing the color plate of conventional molding with the injection molding machine at 350°C to obtain △E.
[0053] (4) Resistance to color change in boiling water: The conventionally formed color plates are boiled in boiling water for 4 hours and then the color difference △E before and after is evaluated.
[0054] (5) Weathering color change: Conventional molded color plates adopt the SAE J2527 automotive exterior method, and the color difference △E before and after is evaluated after 1000 hours.
[0055] Table 1 Component ratio of structural masterbatch
[0056]
[0057] Table 2 Example and comparative example composition ratio and performance test results
[0058]
[0059] It can be seen from the embodiments that the present invention has a significant effect in improving the color change during high-temperature processing, and at the same time, the obtained product also has significantly improved resistance to water boiling discoloration and weather resistance. It can be seen from comparative examples 1 / 2 that without the participation of structural masterbatch, the high-temperature processing color change, water boiling discoloration, and weather resistance discoloration are serious, and more color powder content is required to match the base color. It can be seen from comparative example 3 that the structural color powder needs to be prepared into structural masterbatch, and the dispersion problem of the structural color powder on thermoplastic materials must be solved to achieve the effect. It can be seen from comparative example 4 that deviation from the scheme of the present invention will deteriorate the effect and increase the cost. It can be seen from comparative examples 5 / 6 that in use, it is necessary to select a suitable structural masterbatch according to the melting point of high-temperature nylon, otherwise it will be difficult to achieve liquid crystal orientation dispersion and difficult to match the color.
[0060] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto.
Claims
1. A high-stability colored high-temperature nylon material, characterized in that: The invention comprises the following raw materials in parts by weight: High temperature nylon 40-98 parts; 1-5 parts of structural masterbatch; 1-3 parts of color powder; Filler 0-60 parts; Conventional additives 0.5-5 parts.
2. The high-stability colored high-temperature nylon material according to claim 1, characterized in that: The high temperature nylon is selected from PA6T / 66, PA6T / DT, PA6T / 6I, PA10T, PA9T, PA10T / 66, PA11T homopolymers or copolymers; the melting temperature of the high temperature nylon is 290-340°C.
3. The high-stability colored high-temperature nylon material according to claim 1, characterized in that: The structural color masterbatch comprises the following raw materials in parts by weight: 70-90 parts of carrier resin; 10-30 parts of structural color powder; and 0.5-5 parts of dispersant.
4. The high-stability colored high-temperature nylon material according to claim 3, characterized in that: The carrier resin is a liquid crystal polymer (LCP) with a melting temperature of 270-330°C.
5. The high-stability colored high-temperature nylon material according to claim 3, characterized in that: The melting point of the structural masterbatch is ≤ the melting point of high-temperature nylon.
6. The high-stability colored high-temperature nylon material according to claim 3, characterized in that: The structural color powder is a powdered optical crystal with a periodic micro-nano structure of the size of the wavelength of light; specifically, the metal or its oxide is vacuum-plated to obtain a nano-structured film layer, which is then prepared through processes such as distilled water stripping, ultrasonic crushing, drying, and particle size screening.
7. The high-stability colored high-temperature nylon material according to claim 6, characterized in that: The metal or its oxide includes one or more of aluminum, copper, aluminum oxide, titanium oxide, and iron oxide, and the vacuum plating process includes one or more of vacuum evaporation, sputtering, and magnetron sputtering.
8. The high-stability colored high-temperature nylon material according to claim 3, characterized in that: The dispersant is N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide.
9. According to the high-stability colored high-temperature nylon material of claim 1, the color powder is selected from inorganic pigments, organic pigments, dyes, etc.; from the perspective of high-temperature nylon application, the heat resistance is above 300°C.
10. The high-stability colored high-temperature nylon material according to claim 1, characterized in that: The filler includes reinforcing fiber, powder, flame retardant, etc. The reinforcing fiber includes one or more of glass fiber (GF), aramid fiber (AF), carbon fiber (CF), and basalt fiber (BF); the powder includes one or more of wollastonite, glass microspheres, magnesium sulfate whisker, talcum powder, calcium carbonate, and wood powder; the flame retardant includes one or more of halogen flame retardant, nitrogen flame retardant, and phosphate flame retardant.
11. The high-stability colored high-temperature nylon material according to claim 1, characterized in that: The conventional auxiliary agent includes one or a mixture of lubricants, mold release agents, nucleating agents, antioxidants, light stabilizers, fluorescent brighteners, and toughening agents.
12. The method for preparing the high-stability colored high-temperature nylon material according to any one of claims 1 to 11, characterized in that: The following steps are involved: (1) Preparation of structural color masterbatch: weigh the raw materials according to the formula ratio; add the liquid crystal polymer, structural color powder and dispersant through the main feeding port of the twin-screw extruder after mixing, and obtain the structural color masterbatch after melt extrusion, granulation and drying at a temperature of 300-330° C. for standby use; (2) Preparation of modified materials: After the above-mentioned high-temperature nylon, structural masterbatch, color powder, filler and conventional additives are mixed, except for the reinforcing fiber added from the side feed, the other mixed components are added through the main feed port of the twin-screw extruder, and the composite material is obtained after melt extrusion, granulation, drying and other processes at a temperature of 300-330°C.
Citation Information
Patent Citations
A post-colored polymer cement waterproof coating
CN104556899B
A polyamide composite material, its preparation method and application
CN112358722B
A nylon with high color stability and its preparation method
CN113201216B
A yarn with photonic crystal structure color and its application
CN113897789B
Different colored glass, manufacturing method of different colored glass and light guide plate
CN114524613B